Numerical simulation of flood and debris flows through drainage culvert - paik, Joongcheol; Park, Sang-Deog (Italian journal of engineering geology and environment, 2011)
In mountainous area, cross drainage culvert is commonly used to allow water and debris to pass underneath road or embankment. Flood and debris flows typically undergo a sudden change of the flow depth in the open channel with culvert due to the discontinuity of the bottom slope and the cross-sectional area near the culvert inlet, which can result in culvert failure due to blockage. In this study, we seek to improve our understanding of the culvert flow and its transition in such open channel. A second-order-accurate finite volume method using a shock-capturing scheme with TVD limiters has been developed for solving one dimensional shallow water equations with debris flow resistance terms to predict the time-dependent behavior of non-Newtonian debris flow through culverts. To evaluate the numerical model, we first apply it to calculate a saturated debris flow in a large scale experimental channel. The comparison of the numerical results with experimental measurements shows that the present model can reasonably well reproduce laboratory but fairly large scale debris flows. To investigate the behaviour of the common flood flow, an immature debris flow and debris flow in our laboratory flume with a square culvert and an abrupt change of bed slope, we conducted these ows using corresponding flow resistance relations. The numerical results appear to be in good agreement with our experimental measurements which provide useful information on the debris flow transient through culverts. The numerical results show that the present model is a promising engineering tool for practical simulations of such flows. We elucidate the transient features of ood and debris flows through culverts, based on numerical solutions of such flows in the open channel with culvert at various con gurations of different bottom slopes between the channel and the culvert.